Perception, Temporality And Symbol: A Study Of Man With Cockerel By Ranbir Kaleka (2001-2002) - Kalyanasundaram, Sandhiya (The International Journal of Screendance, 2022)
This article makes an early attempt to emerge a dialogue between neuroscientific theories of perception and video art while proposing alternate lenses to view Kaleka’s installation in the context of Indian contemporary video art. The author proposes that Neuroaesthetics as a field may benefit from studying screendance and audience engagement because the conceptual complexity offered by screendance has the potential to throw light on cognitive and affective systems during emergent aesthetic episodes. Time and symbol, two critical elements that pave the way for new perception, and how these elements transform into materiality in Kaleka’s work are discussed. This discussion reveals in more depth, the illusory loop that Kaleka constructs in order to engage the audience in a deeper and more critical perception of the human condition at the interface of society, politics and economics with the techniques of video art. While the paper places greater emphasis on perception of an artwork by its audience, artists may be able to use the neurocognitive model analysis to develop different engagement strategies with their audiences. The author’s intention is to delve into an expanded investigation of aesthetic experience and perception using the elusive links between art and science.